THE INFLUENCE OF SEGMENTING, TARGETING AND POSITIONING STRATEGIES ON PURCHASING DECISIONS AT YAZZBRAND STORES IN BIREUEN DISTRICT - Yenni Nova Febrian; T. Edyansyah; Mariyudi; Halida Bahri (RADJA PUBLIKA, 2023)
This research aims to see the influence of Segmenting, Targeting and Positioning Strategies on Purchasing Decisions at Yazzbrand Stores in Bireuen Regency. The sampling technique in this research is Purposive Sampling. The sample in this research was 96 consumers who purchased at Yazzbrand stores. The analytical tools used are multiple linear regression tests and hypothesis testing using the t test and F test. The results of the research show that partially the Segmenting and Positioning variables have a positive and significant influence on purchasing decisions at Yazzbrand stores in Bireuen Regency. Meanwhile, the Targeting variable has no effect on purchasing decisions at the Yazzbrand store in Bireuen Regency. Segmenting, Targeting and Positioning variables have a positive and significant effect on purchasing decisions at Yazzbrand stores in Bireuen Regency. Keywords : Segmenting, Targeting, Positioning and Purchase Decision